2014
DOI: 10.1590/s0100-69912014000100006
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of fibrillar components of the extracellular matrix of transversalis fascia and anterior abdominal rectus sheath in men with inguinal hernia

Abstract: the amount of fibrillar extracellular matrix components did not change in patients with and without inguinal hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…For a long time, numerous studies have been developed to search for causes and best method of treatment 1 , 20 . The causes of failure in bringing the abdominal walls together are important research topics 12 , 13 . The incidence of abdominal wall defects in obese patients is high, reaching 30% after laparotomy.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, numerous studies have been developed to search for causes and best method of treatment 1 , 20 . The causes of failure in bringing the abdominal walls together are important research topics 12 , 13 . The incidence of abdominal wall defects in obese patients is high, reaching 30% after laparotomy.…”
Section: Introductionmentioning
confidence: 99%
“…The research concluded that the amount of fibrillar components of the extracellular matrix was not alterated in patients with and without inguinal hernia 14 . …”
Section: Discussionmentioning
confidence: 97%
“…These differences could be related to the role played by collagen fibres on the appearance of diastasis recti and hernias (Blotta et al 2018 ; Mosanya et al 2020 ). Different proportions of collagen fibres have been reported in the anterior rectus sheath of different ethnic populations, namely, an African Nigerian population (Mosanya et al 2020 ), South-American Brazilian population (Casanova, Trindade & Trindade 2009 ; Gonçalves, De Moraes E Silva & Lopes Filho 2014 ) and a European Portuguese population (Blotta et al 2018 ). To move forward on that issue, a study should be designed to compare different ethnic populations regarding histological characteristics of the abdominal wall in postpartum women with and without diastasis recti.…”
Section: Discussionmentioning
confidence: 99%